Nano-pulse stimulation™ therapy (NPS™) is superior to cryoablation in clearing murine melanoma tumors - McDaniel, Amanda; Freimark, Bruce; Navarro, Cebrina; Von Rothstein, Kristin; Gonzalez, Dacia; Linder, Keith; Nuccitelli, Richard (Frontiers in Oncology, 2023)
Background: Nano-Pulse Stimulation™ Therapy (NPS™) is a new, bioelectric modality that applies ultrashort pulses of electric energy to trigger regulated cell death in treated tissues. Instead of initiating necrosis by heating or freezing, NPS therapy permeabilizes intracellular organelles to activate the cell’s own self-destruct pathway of programmed or regulated cell death. Unlike cryotherapies that can both damage structural tissues and diffuse into the periphery beyond the margins of the lesion, NPS only affects cells within the treated zone leaving surrounding tissue and acellular components unaffected. Methods: We generated melanoma tumors in mice by injecting B16-F10 cells intradermally and compared the efficacy and resulting skin damage from Nano-Pulse Stimulation Therapy with that fro cryoablation in clearing these tumors. Results: The results of the study demonstrate that NPS is superior at clearing B16-F10 melanoma lesions. NPS permanently eliminated up to 91% of all tumor lesions with a single treatment compared to cryoablation that only eliminated up to 66%. Importantly, NPS permanently eliminated these lesions with no recurrence and with minimal dermal fibrosis, underlying muscle atrophy, permanent hair follicle loss or other markers of permanent skin damage. Conclusions: These findings suggest that NPS is a promising new modality for the clearance of melanoma tumors and is a more efficacious, less damaging approach than cryoablative methods for the treatment of aggressive malignant tumors.